Innovation and nutritional content analysis in making Kue Lumpur using green broccoli (Brassica oleracea var. italica) puree as substitute ingredient - Andi Hudiah; Ida Fitri Bohari; Rika Riwayani; Slamet Widodo (AcTion: Aceh Nutrition Journal, 2024)
Broccoli is abundant in fiber, vitamins, and minerals and is useful as a complement to main dishes. However, the use of broccoli during baking is still limited. Therefore, an experiment was conducted to explore the use of broccoli as a substitute in the recipe of a traditional cake, Kue Lumpur, as a traditional Indonesian snack for various events. This study aimed to determine how to make green broccoli puree, the process of making Kue Lumpur with green broccoli puree substitution, the response of panelists, and the nutritional content of Kue Lumpur from green broccoli puree substitution. The experimental design research was conducted at Makassar State University from December 2021 to February 2022. The participants were 16 trained panelists. Data collection was carried out using documentation and questionnaires (Scoresheet). The process of making broccoli puree involves separation, blanching, steaming, and mashing in four formulations: F1 (10%), F2 (20%), F3 (30%), and F4 (40%). Data were analyzed using ANOVA and Duncan's t-test. The organoleptic Kue Lumpur with green broccoli puree substitution had significant acceptability (p<0,05) in formula F2 (20% green broccoli puree and 80% potato) according to color, texture, and taste.  In conclusion, Kue Lumpur in formula F2 is very good based on organoleptic and hedonic properties, and shows that the aroma tends to be more fragrant and preferred.